Legality of cryptocurrency in Indonesia / Gunawan Widjaja - Widjaja, Gunawan (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2019)
The existence of cryptocurrency has attracted controvercies world wide. Many people, including Indonesian, had benefit from cryptocurrency, meanwhile there were also more people suffered lost from “investment” in cryptocurrency. The aim of this research was to make clear the legal status of cryptocurrency in Indonesia. This research was a normative legal research. It conducted literature review to obtain the required data. Data obtained and used in this research were secondary data, which consisted of primary, secondary and tertiary legal documents. Data obtained from literature review were analysed using normative comparative method with qualitative approach. The result proved that as currency, the existence of cryptocurrency for payment was legally prohibited. The involvement of Indonesian citizen in the “investment” in form of crytocurrency can be treated as against public policy even though the issuance of such cryptocurrency was subject to foreign applicable laws.